Pendampingan dan Pemberian Motivasi Kepada Orangtua Anak Prasekolah - Zuhrah Taufiqa; Ade Teti Vani; Nadia Dewi; Dessy Abdullah (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
The decision of the Ministry of Education on the recommendation for the age of elementary school students for the school year of 2021/2022 is from the age of 6 years, with an exception for the children of the age of 5-years-and-6-months to 5-years-and-11-months after taking the psychology test for the readiness to enroll in elementary school. The purpose of this community service program was to motivate parents with children under the age of 6 to know about the personality and the readiness of their children before entering school. The program was carried out in 2 stages: the initial survey and motivating. The initial survey was conducted on social media in the form of a question feed. The motivations were given after collecting question material, with the conclusions at the end. The results of this program were shared through social media, in the form of a summary of motivations. Other people can also share this on their social media accounts.